Proceedings of the IV Advanced Ceramics and Applications Conference - Lee, Bill.; Gadow, Rainer; Mitic, Vojislav; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2017)
This is the Proceedings of III Advanced Ceramics and Applications conference, held in Belgrade, Serbia in 2014. It contains 25 papers on various subjects regarding preparation, characterization and application of advanced ceramic materials.
1.Flash sintering of ceramics: a short review -- 2.Ceramic Matrix Composites for High Performance Friction Applications -- 3.Functional Particulated Ionic Liquid-Based Silica Microcapsules -- 4.Reducing Losses in Magnetic Thin Films Through Nanoscale Surface Patterning -- 5.Contemporary Political and Religious Extremists as Destroyers of Ancient Artistic Heritage -- 6.Pumps to save life in cardiac failure -- 7.Application of Ceramic Nanoparticles for Near Infrared Bioimaging -- 8.Contemporary aspects of joint arthroplasties and role of ceramics -- 9.Contemporary dental ceramics -- 10.Intelligent Nanomaterials For Medicine Diagnostic And Therapy Application -- 11.Environmental impact of tributyl-tin biocides on coastal marine systems in the NE Adriatic sea -- 12.Microwave electro ceramic based on magnesium titanates compounds -- 13.Structural, electrical conduction and dielectric studies of mechano-synthesized manganese nanoferrite -- 14.Towards Electronic Materials Fractal Theory -- 15.Study of Nanodimensional Spinel ni0.5zn0.5fe2o4 Ferrite Prepared by Mechanochemical Synthesis -- 16.Off-resonant Raman spectroscopy of ZnS quantum dots -- 17.Influence of preparation method on SOP modes in ZnO doped with CoO nanoparticles -- 18.Structural Properties of Cu - Se - CuSe2 Thin Films -- 19.Mobile platform usage in creating conservation and restoration documentation -- 20.Jewelry as Specific form of Spiritual and Material Culture.
Keywords: Materials; Physical chemistry; Surfaces (Physics).; Renewable energy sources; Nanotechnology; Materials Engineering; Physical Chemistry; Surface and Interface and Thin Film; Renewable Energy; Nanotechnology